Evaluation of Sixty Days of Patients’ Safety Program under Self-Management Protocol among Patients with Acute Coronary Syndrome: A Clinical Trial Study - Zahra Javanvash; Samaneh Nodehi; Azadeh Khani (Patient Safety and Quality Improvement Journal, 2023)
Introduction:The improvement of patient safety and the quality of life in acute coronary syndrome (ACS) patients are the main objectives of health care systems. Self-management education programs are thus considered one of the effective protocols to improve patients’ quality of life. This study aimed to evaluate the effect of the self-management protocol 5A model on elderly ACS patients’ quality of life. Materials and Methods:This clinical trial was conducted on 53 ACS patients of the Cardiology Department, Imam Reza Hospital, Bojnourd, Iran. Patients were selected according to the permutation blocks for two groups: intervention and control. The intervention group received a self-management program based on the 5A model: Assessment, Advisement, Agreement, Assistance, and Arrangement. The two groups answered demographic and LIPAD questionnaires during the admission and after two months of follow-up. Data were analyzed by the SPSS software (version 16). Results:The findings presented that most ACS patients were female, married, and uneducated. All dimensions of quality of life increased significantly after the study process (P<0.05). However, these elevated levels were not statistically different between the two groups during the study (P>0.05). Conclusion:We presented elevated levels of quality of life among ACS cases after the self-management program during the two-month interval. Considering any difference between the two study groups, further research is needed to improve ACS patients’ health levels and quality of life.